REVIEWING THE CAPITAL BUDGETING STUDY OF AIRPORT DEVELOPMENT PROJECT DURING COVID-19 PANDEMIC RECOVERY - Galis Kurnia Afdhila; Eko Rizkianto (Universitas Muhammadiyah Tangerang, 2023)
The Juanda Airport ranks third in terms of overall traffic among airports in Indonesia and holds the second position in passenger volume among the 15 airports managed by PT Angkasa Pura I. Between 2017 and 2021, PT Angkasa Pura I undertook investments aimed at enhancing the level of support provided to clients utilizing air transportation, through the expansion of Juanda Airport. The COVID-19 pandemic has had a significant impact on the number of passengers utilizing Juanda Airport in Indonesia, resulting in a 59.1% decrease. This decline can be attributed to the ongoing pandemic that has adversely affected the country since the start of 2020. Thus, the observed passenger flow diverged from the passenger projections employed in the project's planning. The aim of the present investigation is to perform a comprehensive examination and evaluation of the capital budgeting aspect of the Juanda Airport Investment Project. The present inquiry employs computations related to capital budgeting. These calculations include the internal rate of return (IRR), discounted payback period (PP), net present value (NPV), and profitability index (PI). The profitability of the Juanda Airport investment project has been demonstrated across three distinct financial scenarios, even in the midst of the Covid-19 recovery period.